The impact of R&D subsidies during the crisis - Martin Hud; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This study investigates the impact of R&D subsidies on R&D investment during the past financial crisis. We conduct a treatment effects analysis and show that R&D subsidies increased R&D spending among subsidized small and medium sized firms in Germany during the crisis years. In the first crisis year, the additionality effect induced by public support was, however, smaller than in other years. This temporary decrease may be caused by an altered innovation subsidy scheme in crisis years or by a different innovation investment behavior of the subsidy recipients. We do not find support for the countercyclical innovation subsidy scheme having caused the smaller additionality effect and conclude that it is likely to be driven by subsidy recipient behavior.
urn:nbn:de:bsz:180-madoc-366575
Keywords: C14; C21; G01; H50; O38; 330; R&D; Subsidies; Policy Evaluation; Financial Crisis; Treatment Effects